Coping with Hypertension among Indigenous Peoples in Brazil and the Role of the Primary Care Nurse: A Critical Review from a Transcultural Perspective - Mauricio Viana Gomes Oliveira; Ângela Maria Mendes Abreu; James R. Welch; Carlos E. A. Coimbra (MDPI AG, 2021)
Our objective is to critically review the literature addressing the strategic role of nurses in the daily primary care of arterial hypertension in Indigenous communities in Brazil. We selected studies based on an initial keyword search of major bibliographic indexing databases for the years 2000 to 2020 and manual search. Further selection was based on topical, methodological, and thematic relevance, as well as evaluation of scholarship quality and pertinence to our chosen narrative. The literature demonstrates Indigenous peoples do not receive health services that measure up to national standards in large part due to a marked lack of academic and employer preparation for nurses operating in transcultural settings. Inequities were apparent in recurrent reports of victim-blaming, deficient clinical communication with patients, clinical malpractice, devaluation of hypertension as a problem for Indigenous peoples, insufficient intercultural training for nurses, and discrimination against Indigenous students in nursing education programs. This systemic problem needs to be addressed by universities and the Indigenous Health Care Subsystem in Brazil.